20/20 visions : collaborative planning and placemaking - Charles, Campion (RIBA Publishing, 2018)
20/20 Visions is an inspiring and visually stimulating introduction to the practice of participatory planning, featuring a set of 20 international case studies that illustrate the effectiveness of engaging communities and stakeholders in the participativedesign process